Indigenous Knowledge as a sole data source in habitat selection functions - Rowenna Gryba; Andrew Von Duyke; Henry P. Huntington; Billy Adams; Brower Frantz; Justin Gatten; Qaiyaan Harcharek; Robert Sarren; Greg Henry; Marie Auger-Méthé (Proceedings of the National Academy of Sciences, 2025)
While Indigenous Knowledge (IK) contains a wealth of information on the behavior and habitat use of species, it is rarely included in the species–habitat models frequently used by Western species management authorities. As decisions from these authorities can limit access to species that are important culturally and for subsistence, exclusion of IK in conservation and management frameworks can negatively impact both species and Indigenous communities. In partnership with Iñupiat hunters, we developed methods to statistically characterize IK of species–habitat relationships and developed models that rely solely on IK to identify species habitat use and important areas. We provide methods for different types of IK documentation and for dynamic habitat types (e.g., ice concentration). We apply the method to ringed seals (natchiq in Iñupiaq) in Alaskan waters, a stock for which the designated critical habitat has been debated in part due to minimal inclusion of IK. Our work demonstrates that IK of species–habitat relationships, with the inclusion of dynamic habitat types, expands on existing mapping approaches and provides another method to identify species habitat use and important areas. The results of this work provide a straightforward and meaningful approach to include IK in species management, especially through comanagement processes.